In Vitro Rumen Fermentation and Furans Degradation Potential of Rock Candy Juice and Sugarcane Molasses - Zarnegar, Zohreh; Ebrahimi, Seyed; Naserian, Abbas; Valizadeh, Reza (Indian Journal of Animal Nutrition, 2018)
The present study was conducted to examine the rumen fermentation and furans disappearance potential of rock candy juice (RCJ) and sugarcane molasses (SM). In the first experiment, RCJ was compared with SM by in vitro gas production technique. Presence and disappearance of furans in the liquid substances were also investigated before and at the end of 24 h incubation. In the second experiment, a multi-phasic model was used for the interpretation of gas production profile from molasses, rock candy juice, sugar, barley andcorn grains whereas gas production was measured at 2 min. intervals. There was no significant difference between the two treatments in terms of the molar VFA proportion and acetate to propionate ratio. At the end of fermentation, concentration of ammonia nitrogen was lower (P